COMPARATIVE ANALYSIS OF FINANCIAL PERFORMANCE BETWEEN SHARIA AND CONVENTIONAL BANKING DURING 2017 - 2021 - Mamik Utami (The Scientia Journal of Economics Issues, 2023)
This research aims to find out whether there are differences on the financial performance of Islamic and Conventional banking during 2017 – 2021 by using Mann Whitney U test to analyze the Capital Ratio (CAR), Profitability Ratio (ROA), Asset Quality Ratio (NPF/NPL), Efficiency Ratio (BOPO), Liquidity Ratio (FDR/LDR) and Earning Assets Ratio (NIM). The object of this research is conventional public banking registered by the Financial Services Authority (OJK) and classified to the criteria of BUKU III and BUKU IV which are categorized by type, namely National Private Banks and State-Owned Banks in 2017 - 2021. As for sharia banking registered with OJK which is categorized as a national private bank in 2017 – 2021. This research sample consisted of 19 banks, including 12 conventional banks and 7 Islamic banks in Indonesia. This study used a purposive sampling technique and secondary data obtained from the official banking website and the OJK website. The results of the Mann Whitney test shows that there are significant differences in the ratios of ROA, BOPO and NIM in Islamic and conventional banking. Meanwhile for the CAR, NPL/NPF and LDR/FDR ratios, the results of Mann Whitney test showed there were not significant difference between the performance of Islamic and conventional banking during that period. This research found the results that conventional banking has a better ability in earning profits, managing productive assets, cost efficiency, as well as the ability to fulfill its obligations while Islamic banking had better in using capital to support its assets and the collectibility of its productive assets. Nevertheless, the financial performance of Islamic banks is not significantly different from the financial performance of conventional banks.